Comparison of Clinical Outcomes of Neglected Posterior Elbow Dislocation Managed with Open Reduction With and Without K-Wire Fixation - Luthfi Wal Ilkram; Nino Nasution; Benny (Universitas Muhammadiyah Palu, 2025)
Neglected posterior elbow dislocation presents a significant surgical challenge due to chronic soft tissue contractures and joint stiffness. Open reduction is the standard treatment, but the benefit of additional K-wire fixation remains uncertain. This observational analytic study with a case-control design was conducted at Haji Adam Malik General Hospital, Medan. A total of 50 patients with neglected posterior elbow dislocation treated between January 2020 and December 2024 were included. Patients were divided into two groups: open reduction with K-wire fixation (n = 25) and without fixation (n = 25). Clinical outcomes were assessed using the qDASH score, range of motion (ROM), and joint instability. Data were analyzed using Chi-square and Fisher’s exact tests with a significance level of p < 0.05. There were no significant differences between the two groups in qDASH scores (p = 0.551), ROM (p = 0.529), or joint instability (p = 0.773). Most patients (64%) achieved minimal disability, 72% had normal ROM, and 78% showed no signs of instability postoperatively. Open reduction of neglected posterior elbow dislocation yields comparable functional outcomes with or without K-wire fixation. The addition of K-wire does not appear to significantly influence disability scores, range of motion, or elbow stability. Surgical success may depend more on soft tissue management and rehabilitation than on internal fixation.